The impact of luteal serum progesterone levels on live birth rates—a prospective study of 602 IVF/ICSI cycles. Issue 8 (28th June 2018) - Thomsen, L H; Kesmodel, U S; Erb, K; Bungum, L; Pedersen, D; Hauge, B; Elbæk, H O; Povlsen, B B; Andersen, C Y; Humaidan, P
Abstract: STUDY QUESTION: Is the chance of a live birth following IVF treatment and fresh embryo transfer affected by early and mid-luteal serum progesterone (P4 ) levels? SUMMARY ANSWER: Low as well as high serum P4 levels in the early and mid-luteal phase reduce the chance of a live birth following IVF treatment with fresh embryo transfer. WHAT IS KNOWN ALREADY: Data from non-human studies and studies of frozen–thawed embryo transfer cycles indicate that low as well as high P4 levels during the mid-luteal phase decrease the chance of pregnancy. The altered P4 pattern may disrupt the endometrial maturation leading to asynchrony between embryonic development and endometrial receptivity, thereby, compromising implantation and early development of pregnancy. STUDY DESIGN, SIZE, DURATION: Prospective multicenter cohort study of 602 women undergoing IVF treatment. Patients were recruited from four Danish public Fertility Centers from May 2014 to June 2017. The study population was unselected, thus, representing a normal everyday patient cohort. Patients were treated in a long GnRH-agonist protocol or a GnRH-antagonist protocol and triggered for final oocyte maturation with either hCG or a GnRH-agonist. The same vaginal luteal support regimen was applied in all patients. PARTICIPANTS/MATERIALS, SETTING, METHODS: Serum P4 levels from the early or mid-luteal phase were correlated to positive hCG and live birth rates (delivery > gestational week 20). Patients were divided into four P4 groups based on raw data of P4 serum levels and reproductive outcomes during early luteal phase (P4 <60 nmol/l, P4 60–100 nmol/l, P4 101–400 nmol/l and P4 >400 nmol/l) and during mid-luteal phase (P4 <150 nmol/l, P4 150–250 nmol/l, P4 251–400 nmol/l and P4 >400 nmol/l). MAIN RESULTS AND THE ROLE OF CHANCE: The optimal chance of pregnancy was achieved with serum P4 levels of 60–100 nmol/l in the early luteal phase whereas the optimal P4 level during the mid-luteal phase was 150–250 nmol/l. Below, but most distinctly above these levels, the chance of pregnancy was consistently reduced. With an early luteal P4 level of 60–100 nmol/l, the chance of a positive hCG-test was 73%, 95% CI: [59, 84] following cleavage stage embryo transfer. In contrast, with P4 levels >400 nmol/l, the chance of a positive hCG-test was significantly reduced to 35%, 95% CI: [17, 57], thus, an absolute risk difference of −38%, P = 0.01. A similar negative association between early luteal P4 and live birth rate was found, although it did not reach statistical significance. During the mid-luteal phase, a P4 level of 150–250 nmol/l resulted in an optimal chance of live birth: 54%, 95% CI: [37, 70] compared to 38%, 95% CI: [20, 60] with a P4 level >400 nmol/l, thus, an absolute risk difference of −16%, P = 0.14. All estimates were adjusted for maternal age, maternal BMI, study site, final follicle count and late follicular P4 levels. LIMITATIONS, REASONS FOR CAUTION: This study is the first to explore the possible upper and lower thresholds for luteal P4 following IVF treatment and fresh embryo transfer, and the optimal P4 ranges found in this study should be corroborated in future clinical trials. Furthermore, the P4 thresholds in this study only apply to fresh IVF cycles, using vaginal luteal phase support, as the optimal P4 level in cycles using intramuscular P4 may be different. WIDER IMPLICATIONS OF THE FINDINGS: Future studies are necessary to explore whether additional exogenous luteal P4 supplementation in the low P4 group could increase the chance of a live birth following fresh embryo transfer, and whether patients with luteal P4 levels >400 nmol/l would benefit from segmentation followed by subsequent transfer in frozen/thawed cycles. TRIAL REGISTRATION NUMBER: NCT02129998 (Clinicaltrials.gov). STUDY FUNDING/COMPETING INTEREST(S): L.H.T. received an unrestricted grant from Ferring Pharmaceuticals, Denmark, to support this study. P.H. received unrestricted research grants from MSD, Merck, Gedeon Richter and Ferring Pharmaceuticals outside of this work as well as honoraria for lectures from MSD, Merck and Gedeon Richter outside of this work. U.K. received honoraria for lectures from MSD and Ferring Pharmaceuticals outside of this work. C.A. received unrestricted research grants from MSD, IBSA, and Ferring Pharmaceuticals outside of this work as well as honoraria for lectures from MSD and IBSA. H.O.E. and B.B.P. received an unrestricted research grant from Gedeon Richter outside of this work. K.E., L.B., D.P. and B.H. have no conflict of interest. Furthermore, grants from 'The Health Research Fund of Central Denmark Region', 'The Research Foundation of the Hospital of Central Jutland', 'The Research Foundation of A.P. Møller', 'The Research Foundation of Aase & Ejnar Danielsen', 'The Research Foundation of Dagmar Marshall', 'The Research Foundation of Dir. Jacob Madsen & Hustru Olga Madsen', 'The Research Foundation of Fam. Hede Nielsen' and 'The Danish Medical Research Grant' supported conducting this study. The providers of funding were neither involved in the conduction of the study nor in the writing of the scientific report.